Wildlife management of German colonists in the Don Army region - D. Yu. Shishkina (Юг России: экология, развитие, 2015)
The nature use of German colonists in the Don Forces District. The history of the use of natural resources by the German colonists is considered. Development of the settling system is analyzed, main features of natural resources use and patterns of their evolution are studied.